Assessing the Role of Social Stigma in Relation to the Concept of Social Inclusion and Exclusion - Dhakal, Sachita Sharma (KMC Research Journal, 2017)
Every society has some sort of hierarchy, division or categories. Some underlies within the structures of society, while others are created by the members of the society. Stigma is an unavoidable side of human society where ideal, division and discrimination-less society is just an imagination. This article argues that stigma in various form is generated, accepted in group, and becomes “common mind” to isolate any “other”, offering unequal distribution of opportunity and subjected to the social exclusion. It becomes matter of “we” and “other” and still left silence to become public concern.